Standard colorimetry : definitions, algorithms and software - Oleari, Claudio (Wiley, 2015)
Colour is a sensation and as such it is a subjective and incommunicable quantity. Colour measurement is possible because we can create a correspondence between colour sensations and the light radiations that stimulate them. This correspondence concerns the physics of light radiation, the physiology of the visual process and the psychology of vision. Historically, in parallel to standard colorimetry, systems for colour ordering have been developed that allow colour specifications in a very practical and concrete way, based on the direct vision of material colour samples arranged in colour atlases. Colour-ordering systems are sources of knowledge of colour vision, which integrate standard colorimetry.- Resumé vydavatel
Title from resource description page (Recorded Books, viewed December 14, 2015).
Keywords: kolorimetrie; odraz světla; colorimetry; light reflection; absorpce světla; elektronické knihy; sborníky; electronic books; papers of several authors